Miscellanea Miridologica IV: Taxonomy and chorology of new or little known taxa of Andean and Neotropical Regions (Heteroptera: Miridae) - Chérot, Frédéric (2018)
Guyana and Adnotholopus carapezzai n. sp. is described as new species from Iquitos, Peru. The female genitalic structures of Stenoparedra fallax (Signoret, 1864), S. scutellata (Spinola, 1852) and S. similaris Carvalho and Dutra, 1961 are briefly described for the first time, the genus diagnosed and keyed, the habitus of both sexes of all included species are illustrated. An observation of necrophagy of Stenoparedra on honeybee is briefly discussed. Data on chorology of several species (with geographical coordinates of each new collection events) are also provided, including several new country records: Anomalocornis tucuruiensis Carvalho, 1984 (French Guyana), Calocorisca villosa Distant, 1884 (Ecuador), Dagbertus insignis Carvalho, 1977 (Peru), Eccritotarsus incaicus Carvalho and Gomes, 1970b (Ecuador), Fortunacoris castaneus Carvalho, 1985 (Ecuador), Garganus insularis Carvalho and Becker, 1957 (Costa Rica), Guianella pilosa Maldonado and Carvalho, 1981 (Peru), Laemocoridea dispersa (Carvalho, 1944b) (French Guyana), Notholopus columbianus Carvalho, 1975 (Costa Rica and Peru), N. coreoides Carvalho, 1975 (Surinam), Parafulvius amblytyloides Carvalho, 1954 (French Guyana), Phytocoris araucanus Carvalho and Ferreira, 1969 (Argentina), Polymerus chilensis Carvalho and Gomes, 1969 (Argentina), Preposisca frontosa (Carvalho, 1987) (French Guyana), Rhinacloa apicalis (Reuter, 1905) (French Guyana), R. clavicornis (Reuter, 1905) (French Guyana), R. pallidipes Maldonado, 1969 (French Guyana), Sericophanes ornatus (Berg, 1878) (French Guyana), Stenodema columbiensis (Carvalho, 1985) (Ecuador), Taedia compactina Carvalho, 1975 (Peru) and Tytthus parviceps (Reuter, 1890) (French Guyana).